Психологические особенности женщин с однополой сексуальной ориентацией - Гавриляка, Н.А.; Луценко, Е.Л. (Пенза – Махачкала – Ереван: Научно-издательский центр «Социосфера», 2012)
In this research 15 lesbians and 15 heterosexual Ukrainian women were tested by Bem Sex Role Inventory and projective method “Draw-A-Person Test” in our modification: “Draw-A-Man” and “Draw-A-Woman”. It was found that lesbians have higher androgynous identification and heterosexual women have higher feminine one. The variability of sex identification of lesbians is less wide than one’s of heterosexual women. Lesbians imagine men like weak and feminine, who have not firm basis in the life. Both men and women were imagined by lesbians with signs asociality. Проблема понимания гомосексуальной половой ориентации не теряет своей актуальности, о чем свидетельствуют явно противоположные точки зрения, включающие как отнесение ее к психопатологии, так и к индивидуальным особенностям наряду с леворукостью и т.п.
Psychological features of lesbians
Keywords: lesbians; heterosexual women; psychological features; sex identification; гомосексуальная половая ориентация; психопатология; Полоролевой опросник С. Бем; проективный тест «Нарисуй человека» К. Маховер